Longitudinal relationships between teachers’ utility values and quitting intentions: a person-organization fit perspective - Wang, H; Klassen, RM (Elsevier, 2023)
This five-month, two-wave longitudinal study investigated the direct associations between teachers' utility values and quitting intentions, as well as the indirect associations between utility values and teacher outcomes via perceived person-organization fit. The sample included 1,086 Canadian teachers. Results from the latent change structural equation modeling suggested that teachers’ social and personal utility values at the beginning of the semester were directly and indirectly associated with their quitting intentions, as mediated by perceived person-organization fit. Analyses into the pattern of changes further found that increased social utility values corresponded with increased fit perceptions, yielding decreased intentions to leave current schools.